2009
DOI: 10.1080/08860220802595948
|View full text |Cite
|
Sign up to set email alerts
|

Microalbuminuria—A Biomarker of Renal Microvascular Disease

Abstract: Microalbuminuria (amount greater than 30-300 mg/day) reflects an abnormal glomerular capillary permeability to protein. It is usually dependent upon three mechanisms. First, loss of negatively charged surface of the glomerular capillary wall secondary to circulating toxic substances injury-namely, oxidative stress and proinflammatory cytokines-allows the albumin with negatively charged surface to freely escape into the urine. Second, intraglomerular hypertension and hemodynamic maladjustment secondary to glome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 34 publications
0
33
0
3
Order By: Relevance
“…Microalbuminuria is recognised as a clinical marker of the first stages of nephropathy in type 1 and 2 diabetes [5,6], whereas in essential hypertension it is mainly considered an indicator of cardiovascular risk [1,5]. However, microalbuminuria identifies an already established glomerular damage, which is likely to be preceded by earlier structural and functional alterations undetectable to date, unless by kidney biopsy [7][8][9]. Moreover, a variable percentage of type 2 diabetic patients show an impairment of GFR even in the presence of normal albumin excretion [10].…”
mentioning
confidence: 99%
“…Microalbuminuria is recognised as a clinical marker of the first stages of nephropathy in type 1 and 2 diabetes [5,6], whereas in essential hypertension it is mainly considered an indicator of cardiovascular risk [1,5]. However, microalbuminuria identifies an already established glomerular damage, which is likely to be preceded by earlier structural and functional alterations undetectable to date, unless by kidney biopsy [7][8][9]. Moreover, a variable percentage of type 2 diabetic patients show an impairment of GFR even in the presence of normal albumin excretion [10].…”
mentioning
confidence: 99%
“…We hypothesize that the ensuing development of albuminuria in this model may be as a result of a number of mechanisms. It is possible that glomerular endothelial dysfunction developed, therefore increasing glomerular filtration pressure, leading to protein leakage (17). Reactive oxygen species may have also caused a loss of negatively charged surface of the capillary wall, therefore allowing negatively charged albumin to freely pass through the filtration barrier.…”
Section: Ajp-renal Physiolmentioning
confidence: 99%
“…17 All these markers, in fact, reflect macrovascular disease. However, a combination of any of these markers with renal markers such as microalbuminuria, 18,19 renal functional impairment, and renal pathology may as well indirectly reflect renal microvascular disease.…”
Section: Renal Microvascular Disease Is Underestimated In Renal Diseamentioning
confidence: 99%
“…In this regard, another noninvasive diagnostic tool includes Duplex Doppler sonography to detect renal vascular resistance 31 and microalbuminuria. 18,19 It has recently been demonstrated that the magnitude of renal microvascular disease predicts the therapeutic responsiveness to vasodilator treatment in chronic kidney disease (CKD). A mild degree of renal microvascular disease is associated with a normal or mildly altered vascular homeostasis with an adequate response to vasodilator treatment.…”
Section: Renal Microvascular Disease Is Underestimated In Renal Diseamentioning
confidence: 99%